PENGUATAN KARAKTER PELAJAR PANCASILA DALAM PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM BERBASIS KEARIFAN LOKAL DI MADRASAH IBTIDAIYAH - Faizah, Faizah; Prada, Yoga Dwi; Saidiyah, Hana Rifa (SITTAH: Journal of Primary Education, 2023)
This research departs from the problem of the decline in student character values due to the low strengthening of character values. This study aims to describe the biography of KH. Subkhi and the character of the Pancasila student profile in KH. Subkhi and also the process of strengthening the Pancasila student profile in SKI learning based on local wisdom figures in Temanggung. This study uses a phenomenological approach and qualitative descriptive methods. The object of this study is MIN 1 Temanggung. Data collection was carried out through in-depth interviews, observation, and documentation. The results of this study show three findings. First, KH. Subkhi is a religious figure who grew up with his grandfather and father in the pesantren environment and then inherited his grandfather's generous, critical and independent nature. He founded Barisan Muslim Temanggung (BMT) to fight the Dutch colonizers. Second, KH. Subkhi's character is relevant to the six values of the Pancasila student profile: faith and devotion, cooperation, independence, creativity, critical reasoning, and global diversity. Third, strengthening the Pancasila student profile in SKI learning integrated with the KH. Subkhi's character starts with planning, learning activities, and closing.